2015
DOI: 10.1021/ie504876c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of [60]Fullerene-Poly(glycidyl nitrate) and Its Thermal Decomposition

Abstract: A new energetic fullerene derivative [60]­fullerene-poly­(glycidyl nitrate) (C60-PGN) was synthesized through a modified Bingel reaction of C60 and bromomalonic acid PGN ester in the presence of amino acid and dimethyl sulfoxide. The obtained product was characterized by nuclear magnetic resonance, Fourier transform infrared spectroscopy, and ultraviolet–visible spectroscopy. Results confirmed that C60-PGN was synthesized successfully. The thermal decomposition analysis of C60-PGN was investigated by different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…34,35 Therefore, the thermal stabilities of the prepared samples were investigated via differential thermal analysis (DTA). The DTA analyses were performed under an air ow of 50 mL min À1 with approximately 2 mg of sample and aAl 2 O 3 as the reference material.…”
Section: 33mentioning
confidence: 99%
“…34,35 Therefore, the thermal stabilities of the prepared samples were investigated via differential thermal analysis (DTA). The DTA analyses were performed under an air ow of 50 mL min À1 with approximately 2 mg of sample and aAl 2 O 3 as the reference material.…”
Section: 33mentioning
confidence: 99%
“…In general, C 60 can either be combined with energetic moieties, as shown above, or be functionalized with energetic polymers. Two novel fullerene-based energetic polymers have been prepared recently, including C 60 -poly(glycidyl nitrate) (C 60 -PGN, Cp-16) 120 and C 60 -glycidyl azide polymer (C 60 -GAP, Cp-17).…”
mentioning
confidence: 99%
“…Figure 7 depicts the IR spectra of the thermal decomposition gas at different decomposing temperature. The results showed that the decomposition products were mainly H 2 O (3540 cm –1 ), CO 2 (2360 cm –1 ), N 2 O (2247, 1274 cm –1 ), CO (2148 cm –1 ), and NO 2 (1630, 1590 cm –1 ),17,18 initially, because of the central nitrogen atom of dinitramide anion that bears two strongly electron‐withdrawing groups (nitro group). As the temperature rises, the dinitramide anion decomposed NO 2 firstly.…”
Section: Resultsmentioning
confidence: 99%